Bagaimana Inovasi dan Perdagangan Teknologi Mempengaruhi Kinerja Pertumbuhan Ekonomi di Indonesia? - Fatimah Zahra Nasution; Muhamad Ferdy Firmansyah (Faculty of Economics and Business, Jenderal Soedirman University, 2022)
Economic growth is an increase in the output of each sector in a certain year. Innovation can provide carrying capacity for productivity, efficiency and performance effectiveness in each sector. In an effort to increase output, research and innovation are needed. This study empirically estimates the impact of technological innovation and trade on economic growth. The method used is a quantitative method using Autoregressive Distributed Lag (ARDL) for long-term analysis and Error Correction Model (ECM) for short-term analysis. By using time series data, it is empirically found that in the long-term analysis, the innovation stated in the number of patents will have a significant positive effect on economic growth when technology imports occur. Meanwhile, innovation will have a significantly negative effect in grant financing in the event of an increase in technology trade. This indicates that reducing grants by increasing the quality of research through the efficiency of grants will promote economic growth. On the other hand, in the short-term analysis, innovation has no effect on economic growth, whereas only ICT Export technology can support economic growth. In another empirical analysis it was found that institutions and population growth had no effect on economic growth in terms of innovation and technology. So the government is expected to increase technology transfer abroad for domestic research purposes and increase demand for technology exports to become an incentive for the more effective and efficient use of grant funds.